Logics and rationalisations underpinning entrepreneurial decision-making. Issue 1 (20th February 2017) - Vershinina, Natalia; Barrett, Rowena; McHardy, Peter
Abstract : Purpose: The purpose of this paper is to explore the logics that expert entrepreneurs use when faced with a critical incident threat. Design/methodology/approach: Attempts have been made to define "entrepreneurial logic". This paper is influenced by Sarasvathy's work on high-performance entrepreneurs, which finds that when faced with uncertainty entrepreneurs employ unconventional logic, and encompasses later research acknowledging social contexts where entrepreneurs operate. A typology of decision-making logics is developed, taking into account the situation of crisis. Seven expert entrepreneurs who faced crisis and, despite this, are still successfully operating businesses were interviewed. The paper develops a critical incidents methodology. Findings: Experienced entrepreneurs were found to tend towards causal logic when "the stakes were high" and the decision may affect the survival of their business. They also weigh up options before acting and tend to seek advice from trusted "others" within their network before or after they have made a decision. A mixture of causal and intuitive logic is evident in decisions dealing with internal business problems. Research limitations/implications: The decisions that entrepreneurs make shape and define their business and their ability to recover from crisis. If researchers can develop an understanding of how entrepreneurs make decisions – what information they draw upon, what support systems they use and the logic of their decision-making and rationalisation – then this can be used to help structure support. Originality/value: By exploring decision-making through critical incidents we offer an innovative way to understand context-rich, first-hand experiences and behaviours of entrepreneurs around a focal point.